Coastal evolution : Late Quaternary shoreline morphodynamics - Carter, Bill; Woodroffe, C. D. (Cambridge University Press, 1994)
The shoreline is a rapidly changing interface between the land and the sea. Much of the world's population lives in the coastal zone, and coasts are under threat from a variety of natural and anthropogenic impacts, such as climate or sea-level change. Understanding the natural dynamics of a shoreline is essential in order to assess these ongoing and future impacts. This book is a result of an international initiative to study how coastlines change and how they have evolved over the last few thousand years.